Novos direitos na contemporaneidade - Vol. 1 - Dias, Laércio Fidelis (Editora Oficina Universitária, 2021)
Originated from the "Seminar on Human Rights and New Rights in Contemporaneity", promoted by the Study Group "PACTO - Peace, Culture and Tolerance", held on the premises of the Faculty of Philosophy and Sciences of the Universidade Estadual Paulista (Unesp), campus of Marília, in the city of Marília/SP, on May 4, 2018, this work aims to publish works of an academic-scientific nature on the fundamental theme of human rights and emerging rights in this contemporary era. Adds, among the authors who sign the chapters, researchers from different institutions of higher education, from various academic levels and from fun areas of humanistic knowledge, so that there is ample reflection and analysis of such themes of recognized national and international importance, notably with regard to human rights. The one that we presume to run through the articles is that contemporary society, in Brazil and around the world, undergoes numerous large-scale changes, in customs and values, which have an impact on the issue of rights, and, therefore, demand consideration and investigation. In this sense, New Rights in Contemporaneity, vol. I reveal the university fulfilling its role of stimulating reflection and discussion of themes with dual sexuality: academic-scientific and for society in general. Undoubtedly a rich, thought-provoking read. Whoever walks it carefully will reap tasty and valuable fruits.